SIMBOL VISUAL PADA GUNUNGAN SUNDA SAWAWA DALAM MENCIPTAKAN IDENTITAS KASUNDAAN - Nurun Ala Nurin; Anis Sudjana; Zainudin Ramli (ATRAT: Jurnal Seni Rupa, 2019)
Visual Symbols in the Sunda Sawawa’s Gunungan in Creating Sundanese’s Identity. The purpose of this discussion is to find out how a cultural work is created by not removing standards in the process. The object of research in this study is a wayang golek’s gunungan that began processing it in 2011 and was completed in 2013. The limitations of the problem in the discussion are the meanings and meanings that exist in the object of research. The research method used is the method of description using a theoretical emic approach in anthropological studies to describe the object of research while analyzing the object of research. The result of the research is sunda sawawa’s gunungan is a transformation work from classical gunungan. Signs and meanings in it change according to the meaning and meaning of the meaning given by the conceptor in an effort to give the identity of the Sundanese’s gunungan.Keywords: Gunungan, Symbol, Sign, Meaning________________________________________________________________ Tujuan dari diskusi ini adalah untuk mengetahui bagaimana sebuah karya budaya tradisi tercipta dengan tidak meninggalkan pakem didalam proses penciptaannya. Objek tulisan pada kajian ini adalah sebuah gunungan wayang golek yang mulai diproses penciptaannya sejak tahun 2011 dan selesai pada tahun 2013. Batasan masalah pada diskusi yaitu mengenai tanda dan makna yang ada pada objek kajian. Metode kajian yang digunakan adalah metode deskripsi analisis dengan menggunakan pendekatan teori emik dalam studi antropologi untuk mendeskripsikan objek penelitian sekaligus menganalisa objek diskusi. Hasil kajian adalah gunungan sunda sawawa merupakan karya transformasi dari gunungan klasik. Tanda dan makna di dalamnya berubah sesuai dengan kebutuhan tanda dan makna kebudayaan sunda yang diberikan oleh konseptor sebagai upaya untuk memberikan identitas gunungan sunda. Kata Kunci: Gunungan, Simbol, Tanda, Makna